Childbearing intentions after a very preterm delivery: a study among Portuguese mothers and fathers. (20th October 2021) - Alves, E; Amorim, M; Nogueira, C; Silva, S
Abstract: Background: Adjustments to intended family size are strongly affected by life-course events, but data on childbearing plans after a very preterm delivery are lacking. This study intends to assess the childbearing intentions of mothers and fathers of very preterm infants, regarding the desired and intended number of children, the factors associated with the intention to have more children and the main reasons for not wanting to have more children. Methods: Between May and July 2017, mothers and fathers of very preterm infants were invited to participate in a structured online questionnaire through the Portuguese association of parents for support to the premature baby, and 231 mothers and 21 fathers were included. The discrepancy between the ideal and intended number of children was assessed by the McNemar-Bowker test. To assess the main factors associated with the plan to have more children in the future, unconditional logistic regression models were fitted to compute odds ratios (OR) and 95% confidence intervals (95%CI), adjusted for age, number of children and time after the very preterm delivery. Results: Participants intend to have fewer children than they ideally desired (p < 0.001). Although 69.8% of parents would like to have more children, only 25% actually plan to conceive. After adjustment, participants aged above 34 years (OR = 0.27; 95%CI:0.08-0.86), with more than one offspring (OR = 0.34; 95%CI:0.14-0.69) and who experienced a very preterm delivery 5 or more years ago (OR = 0.28; 95%CI:0.09-0.90) were less likely to report the intention to have more children. The main reasons reported for not wanting to have more children were "having the desired number of children" (38.5%), "financial unavailability" (24.2%) and "being too old to have more children" (20.5%). Conclusions: This study provides a comprehensive assessment of childbearing intentions after a very preterm delivery, advocating for reproductive counselling policies supportive of family planning. Key messages: Discrepancy between the ideal and actual childbearing intentions support the enhancement of reproductive healthcare services for family planning. Socioeconomic and age-related constraints were the main motives presented by mothers and fathers of very preterm infants for not wanting to have more children.